3‐Hydroxybutyrate regulates energy metabolism and induces BDNF expression in cerebral cortical neurons. Issue 5 (14th November 2016) - Marosi, Krisztina; Kim, Sang Woo; Moehl, Keelin; Scheibye‐Knudsen, Morten; Cheng, Aiwu; Cutler, Roy; Camandola, Simonetta; Mattson, Mark P.
Abstract : In response to fasting and vigorous exercise, the ketone 3‐hydroxybutyrate (3OHB) is generated in the liver from fatty acids released from adipocytes. Circulating 3OHB enters the brain where it is transported into neurons by monocarboxylic acid transporter 2 (MCT2) and then enters mitochondria. 3OHB stimulates mitochondrial respiration and reactive oxygen species production, resulting in the activation of the transcription factor NF‐kB which translocates into the nucleus and induces the expression of the Bdnf gene. BDNF is believed to mediate, in part, beneficial effects of exercise and fasting on brain function and resistance to stress and neurodegenerative disease. Abstract: During fasting and vigorous exercise, a shift of brain cell energy substrate utilization from glucose to the ketone 3‐hydroxybutyrate (3OHB) occurs. Studies have shown that 3OHB can protect neurons against excitotoxicity and oxidative stress, but the underlying mechanisms remain unclear. Neurons maintained in the presence of 3OHB exhibited increased oxygen consumption and ATP production, and an elevated NAD + /NADH ratio. We found that 3OHB metabolism increases mitochondrial respiration which drives changes in expression of brain‐derived neurotrophic factor (BDNF) in cultured cerebral cortical neurons. The mechanism by which 3OHB induces Bdnf gene expression involves generation of reactive oxygen species, activation of the transcription factor NF‐κB, and activity of the histone acetyltransferase p300/EP300. Because BDNF plays important roles in synaptic plasticity and neuronal stress resistance, our findings suggest cellular signaling mechanisms by which 3OHB may mediate adaptive responses of neurons to fasting, exercise, and ketogenic diets.